Pregnancy and parenting experiences of women with twin-to-twin transfusion syndrome: a qualitative study - Ren, Lijie; Song, Cancan; Xia, Chunling; Wang, Nan; Yang, Yan; Yin, Shaowei (BMC pregnancy and childbirth, 2021)
Background Qualitative research can reflect the actual thoughts and experience of research subjects and can be used to explore the experiences of women presenting with twin-to-twin transfusion syndrome (TTTS) to facilitate the provision of targeted psychological support. Methods A semi-structured interview method was used to assess the pregnancy and parenting experiences of women with TTTS. Colaizzi method was used for data analysis. Results Eighteen women participated in the study. We found that women with TTTS during pregnancy experienced persistent worry about their children’s health from the disease diagnosis to the subsequent parenting processes, even in case of minor changes in their children’s health. The lack of an efficient referral process and health information increased their uncertainty about their children’s health. Conclusion In addition to the children’s health, other difficulties encountered during pregnancy and parenting may aggravate the pressure. Clinicians in the first-visit hospital and foetal medicine centre should improve the referral process and establish a follow-up system to provide women with health information and psychological support.